Dichotomy between Modernity and Nepalese Education System: A Qualitative Analysis - Bhattarai, Devi Prasad; Khatri, Bishnu Bahadur (NUTA Journal, 2021)
This paper aims to critically assess the impact of modernism upon Nepalese local and indigenous knowledge systems. The paper highlights that modernism is a challenge, as well as an opportunity for the indigenous community and their knowledge systems. This is a challenge because of its potent threats to collapsing the originality and knowledge tradition the local communities have. And, this is an opportunity because of extending and widening its scope and recognition in the global market with a societal or national space. The paper was based on the qualitative research methodology in which numbers of Focus Group Discussion were carried out to generate the data. The paper explores that there is no need for indigenous communities and local knowledge holders to turn back to their tradition by entirely giving up their interests to become a modern one. Nor has there been a compulsion to abandon their oral traditions and wisdom to become an updated modern one. One of the impacts of modernity on Nepali education is privatization which has devalued the local or indigenous knowledge system. The paper, therefore, advises us on an education system that adapts some theoretical concepts that work as a bridge between local/indigenous knowledge system and modern knowledge system enriching local/indigenous knowledge and grasping good ethos of modernity.